2019
DOI: 10.1186/s13104-019-4426-6
|View full text |Cite
|
Sign up to set email alerts
|

Health sciences students knowledge, attitude and practices with chronic kidney disease in Jimma University, Ethiopia: cross-sectional study

Abstract: Objective The objective of this study was to assess knowledge, attitude and practices of undergraduate health sciences students toward chronic kidney disease at Jimma University. Results The overall weighted knowledge, attitude and practices score of the students were 8.6042 (8.26, 8.95), 6.23 (5.93, 6.53) and 2.51 (2.35, 2.67). Many students knew the basic function, symptoms and risk factors of chronic kidney disease. However, the same number of students showed a lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…Resources is one of the vital element to decrease the spread of diseases and improve health services for patients. Kidney disease is now a health problem that kills a thousand individuals without seeing doctors [45]. To mitigate the problem, the ministry of health needs to make a tremendous effort on the health infrastructure and capacity building in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Resources is one of the vital element to decrease the spread of diseases and improve health services for patients. Kidney disease is now a health problem that kills a thousand individuals without seeing doctors [45]. To mitigate the problem, the ministry of health needs to make a tremendous effort on the health infrastructure and capacity building in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Resources is one of the vital element to decrease the spread of diseases and improve health services for patients. Kidney disease is now a health problem that kills a thousand individuals without seeing doctors [47]. To mitigate the problem, the ministry of health needs to make a tremendous effort on the health infrastructure and capacity building in the area.…”
Section: Discussionmentioning
confidence: 99%
“… 47 , 48 Similarly study among Kenyan medical inpatients reported type II (30.5%) was dominant followed by type III (28.8%). 16 Whereas type III was the most prevalent stage (18.2%) and the least was Stage 5 (1.6 %) in Thai type-II DM patients. 17 While in the Chinese DM patients’ Stage 1 was most prevalent followed by Stage 2.…”
Section: Discussionmentioning
confidence: 93%